Improved Brassica rapa reference genome by single-molecule sequencing and chromosome conformation capture technologies. Issue 1 (15th August 2018) - Zhang, Lei; Cai, Xu; Wu, Jian; Liu, Min; Grob, Stefan; Cheng, Feng; Liang, Jianli; Cai, Chengcheng; Liu, Zhiyuan; Liu, Bo; Wang, Fan; Li, Song; et al.
Abstract: Brassica rapa comprises several important cultivated vegetables and oil crops. Current reference genome assemblies of Brassica rapa are quite fragmented and not highly contiguous, thereby limiting extensive genetic and genomic analyses. Here, we report an improved assembly of the B. rapa genome (v3.0) using single-molecule sequencing, optical mapping, and chromosome conformation capture technologies (Hi-C). Relative to the previous reference genomes, our assembly features a contig N50 size of 1.45 Mb, representing a 30-fold improvement. We also identified a new event that occurred in the B. rapa genome 1.2 million years ago, when a long terminal repeat retrotransposon (LTR-RT) expanded. Further analysis refined the relationship of genome blocks and accurately located the centromeres in the B. rapa genome. The B. rapa genome v3.0 will serve as an important community resource for future genetic and genomic studies in B. rapa . This resource will facilitate breeding efforts in B. rapa, as well as comparative genomic analysis with other Brassica species. Genomes: a new map of field mustard: A detailed third-generation genome sequence has been published for Brassica rapa, which includes crops such as napa cabbage, turnips, and bok choy. Older technologies required researchers to stitch together many short sequences. Recently developed methods produce long, high-fidelity sequences. Xiaowu Wang at the Chinese Academy of Agricultural Science and the Shandong Provincial Key Laboratory of Protected Vegetable Molecular Breeding, Hongkun Zheng at Biomarker Technologies Corporation, and coworkers in China assembled the new version using 1498 sequences, compared to the 96, 883 needed for the previous version. These methods provide a significant improvement in the level of detail, and permit mapping of highly repetitive regions, which were nearly impossible to map using older methods. The new sequence will aid breeding efforts, permit better comparisons with other Brassica genomes, and improve our understanding of genome evolution.